2016
DOI: 10.1159/000457903
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Serotonin 3 Receptor Subunit Gene Variants in Antipsychotic-Induced Weight Gain

Abstract: Background: Schizophrenia (SCZ) is a chronic severe neuropsychiatric disorder, where pharmacological treatment has been hindered by adverse effects, including antipsychotic-induced weight gain (AIWG) and related complications. Genetic studies have been exploring the appetite regulation and energy homeostasis pathways in AIWG with some promising leads. The serotonin system has been shown to participate in these pathways. Methods: In the current study, we examined single nucleotide polymorphisms across the serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Though individual APDs have different respective binding affinities at the serotonin receptors, it has been suggested that APD actions at 5HT2a and 5HT2c receptors in the hypothalamus contribute significantly to iatrogenic weight gain (Ballon et al, 2014 ). In contrast, a recent study showed that polymorphisms in serotonin receptor genes HTR3A and HTR3B were not associated with predicting APD-induced weight gain (Zai et al, 2016 ).…”
Section: Central Nervous System Mechanisms Of Intrinsic and Apd-inducmentioning
confidence: 92%
“…Though individual APDs have different respective binding affinities at the serotonin receptors, it has been suggested that APD actions at 5HT2a and 5HT2c receptors in the hypothalamus contribute significantly to iatrogenic weight gain (Ballon et al, 2014 ). In contrast, a recent study showed that polymorphisms in serotonin receptor genes HTR3A and HTR3B were not associated with predicting APD-induced weight gain (Zai et al, 2016 ).…”
Section: Central Nervous System Mechanisms Of Intrinsic and Apd-inducmentioning
confidence: 92%
“…In a study by Yuan et al [ 38 ], several haplotypes of the promoter region of HTR2C were identified and associated with obesity and diabetes. A pharmacogenetic study of other genes of the serotonergic system ( HTR3A, HTR3B ) did not reveal associations with weight gain induced by antipsychotics [ 39 ].…”
Section: Introductionmentioning
confidence: 99%